Clinician's Manual on Restless Legs Syndrome - Buchfuhrer, Mark J. (Springer International Publishing : Imprint: Adis, 2016)
Written by renowned expert in the field, this handbook is an clinically relevant introduction to restless legs syndrome. Comprised of evidence-based recommendations for diagnosis, treatment and long-term disease management, this publication is an ideal educational resource for busy medical professionals and trainees who wish to become more familiar with this relatively common condition. International treatment guidelines and recent drug developments are also included in this concise yet comprehensive overview of the management of restless legs syndrome.